PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI BERBASIS TERAPI PIJAT REFLEKSI KAKI - Chanif -; Khoiriyah - (Universitas Muhammadiyah Semarang, 2017)
Hypertension or high blood pressure is a vascular disorder that results in the supply of oxygen and nutrients carried by the blood to the tissues of the body is inhibited. Hypertension is a major cause of heart failure, stroke, kidney failure. About 20% of the adult population has hypertension, over 90% of them suffer from primary hypertension. Several factors can cause hypertension are lifestyle with the wrong diet, gender, physical exercise, food, stimulants (substances that speed up the body's functions) as well as stress. A wide variety of relaxation techniques already developed one of which is to provide therapeutic foot reflexology.The purpose of this study was to analyze the effectiveness of foot reflexology massage therapy on blood pressure in hypertensive patients in Semarang. The design used in this research is the